Using 222Rn as a tracer of geodynamical processes in underground environments - Valladares, Diego Leonardo (2014)
Radon levels in two old mines in San Luis, Argentina, were measured and analyzed, with the aim to assess the potential use of this radioactive noble gas as a tracer of geological processes in underground environments. La Carolina gold mine and Los Cóndores tungsten mine are today used as tourismmines. CR-39 nuclear track detectors were used for this purpose. Measurements were performed during both winter and summer seasons. The findings show that in these environments, significant radon concentrations are subject to large seasonal fluctuations, due to the strong dependence on natural ventilation with the outside temperature variations. For both mines, higher concentration values of 222Rn were observed in summer than in winter; with an extreme ratio of 2.5 times between summer and winter seasons for Los Cóndores mine. The pattern of radon transport inside La Carolina mine revealed, contrary towhatwas believed, that thismine behaves as a systemwith two entrances located at different levels. However, this feature can only be observed in the winter season, when there is a marked difference between the inside and outside temperatures of the mine. In the case of Los Cóndores mine, the radon concentration pattern distribution is principally established by air current due to chimney-effect in summer and winter seasons. In both cases, the analyses of radon pattern distribution appear as a good method to trace air currents, and then localize unknown ducts, fissures or secondary tunnels in subterranean environments.